Mitigating Climate Change Through Green Finance in Green Buildings – A Comparative Study on the European Union, India, and Cambodia - Patnaik, Sailesh (Digital Repository of Theses, 2026)
The current climate scenario has created an alarming situation around the world. Climate change has been building an inhabitable environment, affecting everyone physically and economically. The unpredictable nature of the climate scenario has been affecting many businesses. The earth’s temperature has been increasing gradually because of greenhouse gases. To control the earth's temperature, every sector has to reduce its emission levels responsibly. To achieve this target, the Paris Agreement was formulated in 2015. Among all sectors contributing to GHG emissions, the construction sector alone contributes 37% of the total GHG emissions globally (UNEP Global Status Report on Building and Construction 2022). The development of green buildings and retrofits, as well as switching from traditional construction methods to green and energy-efficient construction technologies, can help reduce GHG emissions significantly. Green finance has the potential to act as a strong driving force in the development of green buildings. This dissertation investigates the role of green finance mechanisms in promoting sustainable building practices, focusing on identifying deficiencies, analysing practical implications, uncovering barriers and enablers, and evaluating the effectiveness of these financial tools in the construction industry. The study compares three regions—the European Union (EU), India, and Cambodia—each representing different levels of institutional, economic, and regulatory maturity in green finance adoption. A quantitative research approach was used, with data collected through surveys from stakeholders in green finance, including financial institutions, construction firms, developers, and policymakers. The findings reveal significant gaps in awareness, clarity, and effectiveness of current green finance mechanisms in the construction sector. A majority of respondents expressed dissatisfaction with the existing financial tools, highlighting a disconnect between the available mechanisms and the industry's specific needs. Key barriers identified include regulatory complexities, high upfront costs, long payback periods, and perceptions of green finance as high-risk. However, the study also identifies key catalysts, such as government incentives, subsidies, and stakeholder collaboration, that could improve the adoption and implementation of green finance tools. The research further explores the practical implications of green finance, showing that while these mechanisms offer both environmental and economic benefits, inadequate support and guidance hinder their practical application. The study also emphasises the need for a tailored green finance framework to address the shortcomings of existing mechanisms and align financial instruments with global and local sustainability goals.